Orogenic paleofluid flow recorded by discordant detrital zircons in the Caledonian foreland basin of northern Greenland - Morris, G.; Kirkland, Chris; Pease, V. (Geological Society of America, 2015)
Concordant detrital zircon dates from Neoproterozoic to Paleozoic continental slope and trough deposits in northern Greenland indicate Late Archean and Paleoproterozoic sediment sources. Significant numbers of dates are, however, discordant and, together with a few apparently concordant dates, give ages younger than the depositional ages of overlying fossiliferous sediments. The discordance pattern implies partial or total radiogenic-Pb loss during the Middle Devonian, possibly facilitated by postdepositional fluid movement. Such timing of radiogenic-Pb loss is supported by results from a novel modeling method, which indicate that the greatest statistical similarity between concordant and discordant detrital populations occurs when Pb loss is constrained to the interval of 380–390 Ma, i.e., long after deposition. This radiogenic-Pb loss event is interpreted to reflect fluid flow associated with Caledonian orogenic uplift to the east.